Control of tbe angular position of a direct current motor using PID control, fuzzy control and neural control - Canelón, José; Queipo, Nestor (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this study, the angular position of a direct current motor is controlled using three control approaches: PID Control, Fuzzy Control and two different Neural Control approaches. Then, the performance of these controllers is compared under the following criteria: rise time, settling time, percentage overshoot, íntegral of the absolute value of the error and easiness of design Each control1er is first designed based on the mathematical model of the control problem of Interest and then designed using the corresponding experiment of These different control strategies are evaluated under a variety of operating conditions, using the results obtained from computer simulations and the actual experiment of On the mathematical model, step changes of the set point were used, obtaining a similar performance from PID and Neural controllers. Step and sinusoidal changes were used on the experiment. In the first case the PID controller had a better performance but on the second case the best was the Neural controller.